"More person, and, therefore, more satisfied and happy": The affective economy of reading promotion in Chile. Issue 2 (17th June 2021) - Errázuriz, Valentina; García-González, Macarena
Abstract: Reading is often regarded as a public good and an essential part of developing almost every aspect of human potential. In this article, we survey the "affective economies" of literary reading through a textual and visual analysis of documents issued by Chile's Ministry of Education. Through a critical and diffractive reading of these documents with Ahmed's (2004, 2010) and Braidotti's (2018) conceptualizations of the affective, we claim that when reading is presented as beneficial, pleasurable, and promising, an assemblage of exclusion is set into motion. We describe how the affective repertoires in these documents reinforce oppressive and exclusionary neoliberal values under the guise of the promise of future happiness. The pleasure and happiness that can be achieved through literary reading, however, is only accessible to those who are willing to orientate themselves in the "right ways." In this orientation, the cognitive is privileged over the emotional, and readers are supposed to learn to postpone any current demands for the promise of future happiness.